Keltska dediščina v toponimiji jugovzhodnega alpskega prostora - Repanšek, Luka (Linguistica et philologica, 2016)
The monograph ('Celtic Legacy in the Toponymy of South-Eastern Alps') offers a close examination of the South-Western Alpine region for Celtic (specifically Gaulish) linguistic remains in the onomastic landscape. Supported by a rigorous methodological apparatus, the investigation sets out to determine which ancient and contemporary geographical names can securely be pronounced to be etymologically Gaulish, focusing on the historical phonology, morphology, word formation, lexis, the geographical distribution of the relevant place-names, and the specific nature of their integration into the pre-existing toponymic landscape. The monograph is a decisive step forward in the recognition of the distributional character of Celtic linguistic remains in the Celtic East. In the wide time-span and the multifarious nature of the often fragmentary and sensitive linguistic material that it is faced with, this work contributes equally importantly to the field of comparative Celtic and Indo-European linguistics (especially with concern to the paleolinguistic remains in the region), as it does to Slovene onomastic studies and the problem of the constitution of early Slavic and early Romance phonological make-up and the interaction between the two.